Radiolabeled mAbs as Molecular Imaging and/or Therapy Agents Targeting PSMA. (7th February 2018) - Psimadas, Dimitrios; Valotassiou, Varvara; Alexiou, Sotiria; Tsougos, Ioannis; Georgoulias, Panagiotis
ABSTRACT: Molecular imaging and therapy is a rapidly evolving field in research and clinical medicine. The use of the exciting and attractive properties of radioisotopes for imaging and therapy has made Nuclear Medicine very significant when it comes to molecular imaging/therapy. Monoclonal Antibodies (mAbs) on the other hand are very important targeting biomolecules with high affinity that can "carry" the radioisotope of choice. Herein we make a brief overview of the radiolabeled mAbs that target prostate specific membrane antigen (PSMA) and their use in the management of patients with prostate cancer (PCa).